A Frameshift RBM10 Variant Associated With TARP Syndrome - Daicheng, Han; Shiwen, Xia; Jingxuan, Zhang; Junbo, Hu; Bo, Wang (Frontiers in Genetics, 2022)
Abstract TARP syndrome is a rare X-linked genetic condition caused by mutations in the RBM10 gene. Primary clinical characteristics of TARP syndrome include Talipes equinovarus, Atrial septal defect, Robin sequence, and Persistent left superior vena cava. Newly reported cases identified a few novel RBM10 variants and atypical manifestations associated with TARP syndrome, thus expanding the genetic and clinical spectrum of TARP syndrome. Here we report a molecularly confirmed TARP syndrome with distinctive clinical features including pulmonary arteriovenous malformation, single umbilical artery, and coagulopathy. We identified a novel de novo frameshift RBM10 variant that might be associated with his distinctive clinical features.